Chapter Florence 1438: The Encomium of the Florentina Libertas Sent by Poggio Bracciolini to Duke Filippo Maria Visconti - Mullaney, Ann (Atti, 2020)
This article presents the critical editions of two texts: a letter by the Duke of Milan Filippo Maria Visconti (but written on his behalf by Pier Candido Decembrio) sent to Poggio Bracciolini on 28 July 1438; and the response written by Poggio on 15 September. Poggio's letter contains a brief treatise in praise of Florence and of the Florentina libertas. The documents illuminate a crucial episode in the history of Italian Humanism. The article opens with the discussion of these two letters in their wider historical and intellectual context: on the one hand, the characteristically Florentine «civic humanism» which constitutes the background of Poggio's positions; on the other, the political and cultural competition between Florence and Milan during the first half of the 15th century.